2016
DOI: 10.1017/s003329171600057x
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive mood repair, atypical respiratory sinus arrhythmia, and risk of a recurrent major depressive episode among adolescents with prior major depression

Abstract: This study documented that a combination of behavioral and physiological risk factors predicted MDE recurrence in a previously clinically referred sample of adolescents with depression histories. Because mood repair and RSA are malleable, both could be targeted for modification to reduce the risk of recurrent depression in youths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 78 publications
(103 reference statements)
2
24
0
Order By: Relevance
“…Further, our index of life events did not take into account the length of exposure to a given stressor, or multiple exposures to the same stressor across time. Despite these limitations, the association between developmentally early adversities and later physiological dysfunction in the present sample may help to better understand the mood repair difficulties and unfavorable long-term clinical prognosis of youths with pediatric-onset depression (Kovacs et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, our index of life events did not take into account the length of exposure to a given stressor, or multiple exposures to the same stressor across time. Despite these limitations, the association between developmentally early adversities and later physiological dysfunction in the present sample may help to better understand the mood repair difficulties and unfavorable long-term clinical prognosis of youths with pediatric-onset depression (Kovacs et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Maladaptive mood repair responding (by self-report) has been associated with atypical, less flexible RSA (Williams et al, 2015; Kovacs et al, 2016). Overall, it appears that physiological regulatory flexibility in the context of affective challenge may be one contributor to individual differences in competent mood repair performance, which, in turn, may be compromised by exposure to adversities during early development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sadness is thought to be a normative and evolutionarily adaptive response to loss (Beck & Bredemeier, 2016;Hammen, 2005). However, the ability to effectively regulate or attenuate negative affect (NA) following loss is important, as persistent NA can lead to various forms of psychopathology such as depression (Kovacs et al, 2016;Woody & Gibb, 2015). Over the past few decades, several strategies for the regulation of NA have been identified, some of which are considered maladaptive (e.g., suppression) and others adaptive (e.g., reappraisal, distraction) at reducing NA (Aldao, Nolen-Hoeksema, & Schweizer, 2010;Gross, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of resting HRV have demonstrated positive associations with adaptive cognitive responses to NA (Beevers, Ellis, & Reid, 2011;Volokhov & Demaree, 2010) and improved downregulation of arousal in the context of stress (Fabes & Eisenberg, 1997;Hildebrandt, McCall, Engen, & Singer, 2016). RSA withdrawal to sad stimuli also has been associated with the use of distraction in response to sadness (LeMoult, Yoon, & Joorman, 2016), lower levels of maladaptive regulatory strategies (Kovacs et al, 2016;Yaroslavsky et al, 2013Yaroslavsky et al, , 2016, and with improved affect regulation abilities across adolescence (Vasilev, Crowell, Beauchaine, Mead, & Gatzke-Kopp, 2009).…”
Section: Introductionmentioning
confidence: 99%